Results of studies on earthworms and other mesofauna groups in the tadung mountain area, Dak Nong province - Kim Hoi, Huynh Thi (Academia Journal of Biology, 2014)
There are 10 earthworm species and 18 other mesofauna groups investigated in soil of the Tadung mountain area, Dacplao commune, Dacnong province. Pheretima is the genus that has the highest species number (8 species). Drawida and Pontoscolex have the lowest species number (1 species). The individual number and the bio-mass of eathworms and other mesofauna groups per m2 are found. The species composition of earthworms at high altitude is more abundant than at low altitude. In forest and rice land, earthworms and other mesofauna groups almost distribute in the depth of 0-10cm.